The Genomic and Genetic Toolbox of the Teleost Medaka (Oryzias latipes). Issue 4 (1st April 2015) - Kirchmaier, Stephan; Naruse, Kiyoshi; Wittbrodt, Joachim; Loosli, Felix
Abstract: The Japanese medaka, Oryzias latipes, is a vertebrate teleost model with a long history of genetic research. A number of unique features and established resources distinguish medaka from other vertebrate model systems. A large number of laboratory strains from different locations are available. Due to a high tolerance to inbreeding, many highly inbred strains have been established, thus providing a rich resource for genetic studies. Furthermore, closely related species native to different habitats in Southeast Asia permit comparative evolutionary studies. The transparency of embryos, larvae, and juveniles allows a detailed in vivo analysis of development. New tools to study diverse aspects of medaka biology are constantly being generated. Thus, medaka has become an important vertebrate model organism to study development, behavior, and physiology. In this review, we provide a comprehensive overview of established genetic and molecular-genetic tools that render medaka fish a full-fledged vertebrate system.